Pointing Device Performance in Steering Tasks. - Senanayake, Ransalu; Goonetilleke, Ravindra S. (Perceptual & Motor Skills, 2016)
Use of touch-screen-based interactions is growing rapidly. Hence, knowing the maneuvering efficacy of touch screens relative to other pointing devices is of great importance in the context of graphical user interfaces. Movement time, accuracy, and user preferences of four pointing device settings were evaluated on a computer with 14 participants aged 20.1 ± 3.13 years. It was found that, depending on the difficulty of the task, the optimal settings differ for ballistic and visual control tasks. With a touch screen, resting the arm increased movement time for steering tasks. When both performance and comfort are considered, whether to use a mouse or a touch screen for person--computer interaction depends on the steering difficulty. Hence, a input device should be chosen based on the application, and should be optimized to match the graphical user interface.